Coastal carbonate system variability along an active lava–seawater interface - González-Santana, David; Santana-Casiano, Juana Magdalena; González, Aridane G.; González-Dávila, Melchor (Frontiers in Marine Science, 2022)
Lava flows from the 2021 volcanic eruption in La Palma, Canary Islands, reached the shoreline during three events on September 28th, November 10th, and November 22nd, strongly affecting the seawater properties as they interacted with the seawater. The evolution of surface and water column physicochemical properties (temperature, salinity, carbonate system variables, and dissolved oxygen) was characterized during 13 visits to the frontal zone of the newly formed deltas. A large volume of hot (50°C measured on November 12th) and high salinity seawater promoted pH values in the frontal zone of 7.0 with important decreases in alkalinity, ΔAT, and total dissolved inorganic carbon, ΔCT, that reached 566 and 272 µmol kg−1, respectively. The addition of acids generated during the lava–seawater interaction (44.4 mmol), together with those used in the titration of carbonate alkalinity (796 ± 72 mmol) plus acids used in metal dissolution (21 mmol), was estimated with an average added proton concentration of 0.31 µmol kg−1 of seawater in the affected 2.7 · 106 m3 for November 12th. During this event, the decrease in pH and the increase in temperature increased the partial pressure of CO2, outgassing 2 tons of CO2, 40 times the daily emitted CO2 for this area under non-eruptive conditions. One month after the eruption, the studied physicochemical properties of the seawater close to the new deltas returned to the usual non-eruptive normal values, which include the presence of low salinity, low pH, and high CO2 gas diffusive emissions through submarine groundwater discharges observed between the formed deltas. The new mineral-rich deltas and the increase in solubility due to the low pH conditions contributed to the recovery of the affected area.